Mixed oats and alfalfa improved the antioxidant activity of mutton and the performance of goats by affecting intestinal microbiota - Sun, Yukun; Hou, Tingyi; Yu, Qingyuan; Zhang, Chengrui; Zhang, Yonggen; Xu, Lijun (Frontiers in Microbiology, 2023)
Oat hay and alfalfa hay are important roughage resources in livestock production. However, the effect of the mixture of oat hay and alfalfa hay on the meat quality of Albas goats is unclear. This study aimed to investigate the effects of feeding different proportions of oat hay and alfalfa hay on the growth performance and meat quality of Albas goats. Furthermore, to clarify the relationship between the rumen and cecal microbes on performance and meat quality by analyzing the rumen and hindgut microbiomes. Thirty-two goats were fed for 70 days and divided into whole oat group, oat alfalfa ratio 3:7 group (OA73), oat alfalfa ratio 7:3 group (OA37) and whole alfalfa group, with 8 goats in each group. The results showed that feeding alfalfa could significantly reduce the daily gain of fattening goats. Compared with the highest group, the daily gain decreased by 19.21%. Although there was no significant change in feed intake, the feed conversion rate of the whole alfalfa group was significantly decreased by 30.24%-36.47%. However, with the increase of alfalfa content, T-AOC and MDA showed a trend change, and the antioxidant activity of fattened goat meat fed with the high alfalfa group was significantly higher than that of the low alfalfa group. Notably, the abundance of Bacteroidales_unclassified and Clostridium were strongly correlated with T-AOC and MDA. Therefore, increasing the proportion of alfalfa in the diet can affect the antioxidant activity of goat meat by improving the gut microbiota, while oat hay mixture can improve the growth performance of livestock.